Theory and Applications of CT Imaging and Analysis - Homma, Noriyasu (IntechOpen, 2011)
The x-ray computed tomography (CT) is well known as a useful imaging method and thus CT images have continuingly been used for many applications, especially in medical fields. This book discloses recent advances and new ideas in theories and applications for CT imaging and its analysis. The 16 chapters selected in this book cover not only the major topics of CT imaging and analysis in medical fields, but also some advanced applications for forensic and industrial purposes. These chapters propose state-of-the-art approaches and cutting-edge research results.